Synthetic chiral vortices for highly-sensitive chiral discrimination - Mayer, N.; Ayuso, D.; Ivanov, M.; Smirnova, Olga (Optics InfoBase Conference Papers, 2022)
We combine bicircular vortex beams, creating light that displays chirality in the dipole approximation with azimuthally varying handedness. The chiral vortex leads to a robust and highly-sensitive response in molecular enantiomers with topological properties.
CRIS-Team Scopus Importer:2023-04-20